Clinical outcomes and uroflowmetry assessment in patients with apical prolapse after laparoscopic uterosacral ligament suspension. (April 2021) - Ma, Yidi; Zhang, Ye; Ma, Congcong; Wang, Yuan; Tian, Weijie; Zhu, Lan
Abstract: Objective: The aim was to evaluate the voiding function and voiding dysfunction 3 months after laparoscopic uterosacral ligament suspension (LUSLS). We identified risk factors for postoperative voiding dysfunction. Study design: This retrospective study included 57 women with apical prolapse who underwent LUSLS with stage II or greater apical prolapse and without advanced anterior vaginal prolapse (stage III or IV). Data were collected from electronic medical records. Voiding function was assessed by uroflowmetry, PVR examination, and self-report questionnaires (the Pelvic Floor Distress Inventory-20 and the Urinary Impact Questionnaire) at baseline and 3 months after surgery. Voiding dysfunction was defined as an average flow rate (Qave)＜10 ml/s, a maximum flow rate (Qmax)＜15 ml/s, or a postvoid residual volume (PVR)＞50 ml. Statistical analyses were performed using paired-sample t tests, χ2 tests, and multivariate logistic regression. Results: Thirty-five percent of women suffered from voiding dysfunction preoperatively. Uroflowmetry parameters and PVR, objective symptoms including voiding difficulties, incomplete empty, frequency and urinary incontinence didn't show significant improvement postoperatively (all p ＞0.05). Low Qave was identified as an independent risk factor of post voiding dysfunction (odds ratio, 0.558; 95 % CI, 0.324−0.963). Conclusions: Approximately one-third of women suffering from apical prolapse without advanced anterior vaginal wall had evidence of voiding dysfunction preoperatively. LUSLS has no obvious effect on uroflowmetry parameters and clinical symptoms.